Factors That Influence Resilience among First-Year Undergraduate Nursing Students: A Cross-Sectional Descriptive Study - Gopolang Gause; Leepile Alfred Sehularo; Molekodi Jacob Matsipane (MDPI AG, 2024)
During their transition from basic to higher education, first-year undergraduate nursing students need to balance theoretical and clinical requirements, as well as their social life. A significant number of them struggle with this, due to a lack of coping mechanisms due to poor resilience. This study aimed to determine factors that influence resilience among first-year undergraduate nursing students at a South African university. A cross-sectional descriptive research design was followed, with stratified convenient sampling. Data were collected during August 2023 using an adapted self-administered online questionnaire. The reliability and validity of the adapted version was ensured in the context of this study. Principal component analysis and varimax rotation were used to analyse data. A total of 123 participants (47.2% from campus A and 52.8% from campus B) completed the questionnaire. The majority (88%) were females. This study showed that resilience can be dependent on various factors, such as lecturer support, parental support, academic achievement, peer and mentor support, optimism about the future, and self-determination. It is recommended that higher education institutions should consider incorporating the factors presented in this study as part of the broader orientation of first-year undergraduate nursing students when they first arrive at university.